Pengembangan Kurikulum Berorientasi Karakter: Membangun Sikap dan Nilai Positif Pada Siswa - Mufidah, Nur; Parmujianto, Parmujianto (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Article History Received: Revised: Published: Keywords: Development, Curriculum, Character The curriculum is an important component in education because the curriculum contains aspects of educational goals which include aspects of knowledge, attitudes and character that are developed. The purpose of this research is to 1) describe the curriculum development process. 2) the students' positive attitudes and values. 3) development of a curriculum oriented towards students' positive attitudes and values. This research uses the library research method, namely collecting data by understanding and studying theories from various relevant literature as a source of information as well as answering the problem formulation regarding the theme being studied. This research discusses 1) the curriculum development process through: a) identifying needs. b) needs analysis. c) preparing a curriculum design. d) validating the curriculum. e) curriculum implementation. f) evaluating the curriculum. 2) Positive characters and values that students must have include religious attitudes, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, love of the country, respect for achievements, friendship, love of peace, love of reading , environmental care, social care and responsibility. 3) the development of a character-oriented curriculum, namely with several efforts: 1) teacher example 2) familiarization with activities at school including daily, weekly, monthly and annual activities.